A Framework for Water Security Data Gathering Strategies (2022)
At the international level, the term “water security” (WS) has gained increasing attention in recent decades. At the operational level, WS is assessed using tools that define the concept using a variety of dimensions and sub-dimensions, with qualitative and quantitative indicators and parameters. The breadth of tools and concepts is an obstacle to the operationalisation of the concept of water security (WS). Clearly, we need a range of diverse data to evaluate water security (WS). However, there are several barriers to designing an optimal Data Gathering Strategy (DGS). Such a strategy must strike a balance between a wide range of competing and overlapping data requirements and characteristics including: resources, information, and impact. The proposed framework aims at filling the existing gaps, not by providing a strict procedure, but instead acting as a “compass”: five interfaces between data and context are identified to orient practitioners towards an optimal DGS. The conceptual aim of the framework can be summarised as shifting the focus of the DGS from a “data-to-information approach” to a “data-to-action approach,” therefore stressing the importance of reaching key stakeholders with information. The specific aims of this paper are to: identify the key issues that should be addressed in designing a Data Gathering Strategy for Water Security (DGSxWS); communicate the key issues with a clear conceptual framework; and suggest approaches and activities that could help water practitioners in dealing with the issues identified. © 2022 by the authors.